Influence of high intensity interval training under hypoxic compared to normoxic conditions on power output during a set of time trails - de Marees, M.; Cohrs, J.; Platen, P.; Mester, J. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: In sports like cross country sprint events where athletes perform three to five time trails separated by 20 min breaks, the ability to regenerate is one key factor for athletes to compete successfully. The enhancing effect of high intensity interval training under hypoxic (HIITH) compared to normoxic conditions on repeated sprint ability was shown by Faiss et all (1). The questioned raised, whether HIIT under hypoxic conditions may even lead to superior results on repeated time trail ability. Methods: 10 endurance trained athletes were randomly divided into a hypoxic (HG FiO2 15%) and normoxic (NG FiO2 19.7%) group. They were blinded to the training conditions. Ahead (pre PT) and after (post PT) the training period performance tests were conducted on a cycle ergometer. Tests included a ramp test followed by three time trails (TT) of four min separated by a break of 20 min. HIIT consisted of two sessions per week for three weeks. Sessions included 10 min of low intensity cycling followed by n=12 (for the first four sessions) and n=14 (for the last two bouts) 15-sec allout- sprints interjected by a break of 45 sec. Power output (PO), heart rate (HR) and lactate concentration (LC) were measured. Results: There were an increase for PO in post PT compered to pre PT for both groups detected. No significant differences were found for any of the analyzed parameters between HG and NG. 30% of the athletes estimated the conditions in which they trained wrong. Conclusion: Six trainings sessions of HIITH didn´t lead to superior results compared to the same training regime under normoxia concerning power output, lactate blood concentration, and heart rate during a set of time trials. As we expected higher effects of hypoxic compared to normoxic training we hypothesize that hypoxic training load (two sessions per week for three weeks with a total hypoxic exposure time of (256 min), the delayed time of post PT (ten days after the last trainings session instead of five days according to Voigt et al (2) may have influenced PO development during the TT.